Perinatal mortality and other severe adverse outcomes following planned birth at 39 weeks versus expectant management in low-risk women: a population based cohort studyResearch in context - Kylie Crawford; Waldemar A. Carlo; Anthony Odibo; Aris Papageorghiou; William Tarnow-Mordi; Sailesh Kumar (EClinicalMedicine)
Summary: Background: Planned birth by induction of labour in low-risk, nulliparous women at 39+0–39+6 weeks gestation is associated with fewer caesarean sections, adverse maternal and neonatal outcomes and perinatal deaths compared with expectant management. However, the consequences of scheduled caesarean section in these women at this gestation are unclear. We compared outcomes following planned birth at 39+0–39+6 weeks gestation (either by induction of labour or scheduled caesarean section) to expectant management. Methods: The population included low-risk, singleton pregnancies between 2000 and 2021 in Queensland, Australia. Study outcomes were perinatal mortality (antepartum or intrapartum stillbirth and neonatal death), severe neonatal neurological morbidity and non-neurological morbidity, severe maternal outcome, maternal-infant separation, perineal trauma, shoulder dystocia, and caesarean birth. Multivariable models were built to determine risks of adverse outcomes for planned birth compared to expectant management. Subgroup analyses according to parity and birthweight were also performed. We calculated the number of planned births required that were associated with one less adverse outcome. Findings: In 472,520 low-risk pregnancies, planned birth at 39+0–39+6 weeks occurred in 97,438 (20.6%) women, of whom 39,697 (40.7%) underwent induction of labour and 57,741 (59.3%) had scheduled caesarean delivery. Planned birth was associated with 52% lower odds of perinatal mortality (adjusted Odds Ratio (aOR) 0.48; 95% CI 0.30, 0.76, p = 0.002), 62% lower odds of antepartum stillbirth (aOR 0.38; 95% CI 0.15, 0.97, p = 0.04), and 84% lower odds of intrapartum stillbirth by (aOR 0.16; 95% CI 0.04, 0.66, p = 0.01). It was also associated with reduction in the odds of severe neurological morbidity (aOR 0.46; 95% CI 0.39, 0.53, p = 0.00004), severe non-neurological morbidity (aOR 0.65; 95% CI 0.62, 0.68, p = 0.00004), and severe maternal outcome (aOR 0.95; 95% CI 0.92, 0.99, p = 0.008) but not maternal-infant separation (aOR 1.04; 95% CI 1.00, 1.08, p = 0.08). The reduction in odds for perinatal mortality, severe neurological, and non-neurological morbidity was greatest for birth by scheduled caesarean section. Compared to expectant management, planned birth by induction of labour was associated with reduced odds of caesarean delivery (aOR 0.54; 95% CI 0.51, 0.58, p = 0.00004), severe perineal trauma (aOR 0.53; 95% CI 0.45, 0.63, p = 0.00004), and shoulder dystocia (aOR 0.73; 95% CI 0.64, 0.84, p = 0.00004). Planned delivery of 2278 (95% CI 1760, 3231) women is associated with a reduction in one case of perinatal death, however significantly lower numbers are required for the other outcomes. Interpretation: Planned birth at 39+0–39+6 weeks in low-risk women was associated with lower odds of perinatal mortality and other adverse outcomes. Reductions in odds of adverse outcome were greater following scheduled caesarean section than induction of labour. Compared to expectant management, induction of labour was associated with lower odds of severe perineal trauma, shoulder dystocia, and caesarean birth. These findings generate further hypotheses that need to be tested in adequately powered randomised controlled trials. Funding: This study was supported by funds from the National Health and Medical Research Council and Mater Foundation.